North-South Technology Diffusion, Regional Integration, and the Dynamics of the ?Natural Trading Partners? Hypothesis - Maurice Schiff; Yanling Wang (Institute for the Study of Labor (IZA), 2004)
Based on static analysis, a number of studies argue that forming a RTA is more likely to raise welfare if member countries are ?natural trading partners,? while other studies claim the opposite. This paper considers the argument from a dynamic viewpoint by examining the impact of trade with Japan, North America and the EU on technology diffusion and TFP in Korea, Mexico and Poland. Using industry-level data, we show that i) technology diffusion and productivity gains tend to be regional: Korea (Mexico) (Poland) benefits mainly from trade with Japan (North America) (the EU); and ii) the dynamic version of the ?natural trading partners? hypothesis seems to hold for Korea and Mexico though not necessarily for Poland.
Keywords: O39; F15; F13; F02; F43; 330; North-South technology diffusion; productivity; regional integration; natural trading partners; Korea; Mexico; Poland; Nord-Süd-Beziehungen; Technologietransfer; Handelsregionalismus; Produktivität; Welt